Computational fluid dynamics analysis of a modified Savonius rotor and optimization using response surface methodology. Issue 5 (October 2017) - Moazam Sheikh, Haris; Shabbir, Zeeshan; Ahmed, Hassan; Waseem, Muhammad Hamza; Sheikh, Muhammad Zubair
This article aims to present a two-dimensional parametric analysis of a modified Savonius wind turbine using computational fluid dynamics. The effects of three independent parameters of the rotor, namely, shape factor, overlap ratio, and tip speed ratio on turbine performance were studied and then optimized for maximum coefficient of performance using response surface methodology. The rotor performance was analyzed over specific domains of the parameters under study, and three-variable Box-Behnken design was used for design of experiment. The specific parametric combinations as per design of experiment were simulated using ANSYS Fluent ®, and the response variable, coefficient of performance (Cp ), was calculated. The sliding mesh model was utilized, and the flow was simulated using Shear Stress Transport (SST) k − ω model. The model was validated using past experimental results and found to predict parametric effects accurately. Minitab ® and ReliaSoft DOE++ ® were used to develop regression equation and find the optimum combination of parameters for coefficient of performance over the specified parametric domains using response surface methodology.